Mechanical thrombectomy using the retrograde semi-retrieval technique for patients with underlying intracranial atherosclerotic stenosis - Wang, Wei; Xu, Yongbo; Zhang, Bohao; Liu, Shuling; Ma, Zhenjian; Wang, Sifei; Zhang, Pinyuan; Wei, Ming (Frontiers in Neurology, 2024)
The Retrograde Semi-Retrieval Technique (RESET) has been described as a modified technique for endovascular thrombectomy (EVT) whose safety and efficacy for intracranial atherosclerosis stenosis (ICAS) patients remain uncertain. This article presents our single-center experience, comparing RESET versus non-RESET in ICAS patients. Materials and Methods: We analyzed 327 consecutive ICAS patients who underwent EVT at Tianjin Huanhu Hospital from January 2018 and December 2022. Patients were categorized into two groups: RESET and non-RESET. The primary outcome were the first pass effect (FPE). Secondary outcomes included successful reperfusion, functional independence at 90 days, mortality and symptomatic intracranial hemorrhage (sICH). Results: RESET was significantly associated with FPE (adjusted odds ratio (aOR) 2.00, 95% confidence interval (CI) 1.03-3.87, p=0.040). RESET was not significantly associated with successful reperfusion (aOR 1.5, CI 0.55-4.06, p=0.425), mRS 0-2 at 90 days (aOR 1.36, CI 0.83-2.21, p=0.223), sICH (aOR 0.39, CI 0.12-1.23, p=0.108) and mortality (aOR 0.49, p=0.193). After propensity score matching, the results were consistent with the primary analysis. Conclusion: Compared to non-RESET, patients treated with RESET showed increased FPE incidence and significantly decreased puncture-to-reperfusion time. RESET was proved to be safe and effective in enhancing reperfusion for LVO patients receiving EVT with underlying ICAS.